Losing Credibility : The Stabilization Blues - Guidotti, Pablo (IMF Working Papers; Working Paper ;, 1992)
In exchange rate-based stabilization programs, credibility often follows a distinct time pattern. At first it rises as the highly visible nominal anchor provides a sense of stability and hopes run high for a permanent solution to the fiscal problems. Later, as the domestic currency appreciates in real terms and the fiscal problems are not fully resolved, the credibility of the program falls, sometimes precipitously. This paper develops a political-economy model that focuses on the evolution of credibility over time, and is consistent with the pattern just described. Inflation inertia and costly budget negotiations play a key role in the model.